How Luther became the reformer - Helmer, Christine 1965- (Louisville, KY Westminster John Knox Press, 2019)
History and story: an introduction -- The experience of justification -- How Luther became the reformer -- Modernity and its contradictions -- A test case of anti-Judaism -- How Luther became the reformer (lowercase) of Catholicism -- Reformation.
Includes bibliographical references and index
Keywords: Luther, Martin -- 1483-1546; Luther, Martin -- 1483-1546 -- Influence; Luther, Martin; RELIGION / Christianity / Protestant; Influence (Literary, artistic, etc.); Germany; Electronic books